Migration Aspirations among NEETs in Selected MENA Countries - Raul Ramos (Institute of Labor Economics (IZA), 2017)
The Middle East and North Africa (MENA) region shows high levels of unemployment rates among youth and the rate of youth not in education, employment or training (NEET) is also among the highest in the world. In this context, one of the more obvious reactions of youth facing unmet aspirations in the labour market is migration. The objective of the paper is to analyse the determinants of intentions to migrate of youth NEETs during their school-to-work transitions in selected MENA countries. With this aim, I use microdata from School-to-Work Transition Surveys (SWTS) conducted by the International Labour Organization (ILO) in 2013-2015 in Egypt, Jordan, Lebanon, Palestine and Tunisia. These surveys targeted a nationally representative sample of young people between 15 and 29 and collected data on intentions to migrate (internal and international) and different factors related to their social and educational background. Microeconometric models are used to achieve a better understanding of factors influencing youth's decision to migrate.
Keywords: F22; J61; J65; R23; 330; inactivity; unemployment; NEETs; youth; intentions to migrate; school-to-work transition